Critical analysis of international law failures in the Russian invasion of Ukraine: implications for global security (Law and Safety, 2024)
This paper offers a critical analysis of the structural deficiencies in international law that Russia’s full-scale invasion of Ukraine revealed in 2022. The study reveals a significant failure of international legal mechanisms, in particular the United Nations, to effectively deter Russian aggression and prevent the escalation of violence. Despite numerous legal actions and international responses – including resolutions by the United Nations General Assembly, proceedings at the International Court of Justice and investigations by the International Criminal Court – these measures have failed to alter Russia’s conduct or prevent further deterioration of the situation in Ukraine.The study employs a normative juridical approach, analyzing the legality of Russia’s actions considering established international norms and principles. Through this methodology, the research uncovers how Russia’s justifications for its military intervention – based on self-defense, collective self-defense, and allegations of genocide – are legally flawed and inconsistent with international law. Moreover, the research reveals the broader implications of these violations, including the potential erosion of global legal norms and the setting of dangerous precedents that could undermine international peace and security.The findings of this research highlight the urgent need for reform within the international legal framework to address these deficiencies. The paper concludes by proposing specific reforms, such as expanding the abstention obligation in the United Nations Security Council and clarifying the legal basis for humanitarian intervention, to strengthen the enforcement of international law and better protect state sovereignty. These insights contribute to the ongoing discourse on the role of international law in conflict resolution and the maintenance of global security.
Keywords: Russian Invasion; War in Ukraine; Breach of International Law; Illegality of Russian Actions; Unjustified Claims by Russia.